Operational definitions of successful aging: a systematic review. (March 2014) - Cosco, Theodore D.; Prina, A. Matthew; Perales, Jaime; Stephan, Blossom C. M.; Brayne, Carol
ABSTRACT Background: Half a century after the inception of the term "successful aging (SA), " a consensus definition has not emerged. The current study aims to provide a comprehensive snapshot of operational definitions of SA. Methods: A systematic review across MedLine, PsycInfo, CINAHL, EMBASE, and ISI Web of Knowledge of quantitative operational definitions of SA was conducted. Results: Of the 105 operational definitions, across 84 included studies using unique models, 92.4% (97) included physiological constructs (e.g. physical functioning), 49.5% (52) engagement constructs (e.g. involvement in voluntary work), 48.6% (51) well-being constructs (e.g. life satisfaction), 25.7% (27) personal resources (e.g. resilience), and 5.7% (6) extrinsic factors (e.g. finances). Thirty-four definitions consisted of a single construct, 28 of two constructs, 27 of three constructs, 13 of four constructs, and two of five constructs. The operational definitions utilized in the included studies identify between <1% and >90% of study participants as successfully aging. Conclusions: The heterogeneity of these results strongly suggests the multidimensionality of SA and the difficulty in categorizing usual versus successful aging. Although the majority of operationalizations reveal a biomedical focus, studies increasingly use psychosocial and lay components. Lack of consistency in the definition of SA is a fundamental weakness of SA research.